The effects of government and state ownership on dividends - Siti Salwani Abdullah; Ahmad Ridhuwan Abdullah; Razman Hafifi Redzuan (2014)
This study aims to investigate the relationship between government ownership and dividend policy of Malaysian listed companies. Specifically, the objective of the study is to examine whether government and state ownerships influence dividend payout and dividend per share. The study used a sample of 400 companies, which were randomly chosen. Two dependent variables were used as a proxy for dividend namely the dividend per share (DPS) and dividend payout ratio (DPR), while 8 government agencies (EPF, LTH, KWAP, LTAT, MKD, KNB, PNB and STATE) represented government ownership. Since dividends are truncated, the Tobit model was utilized to examine the effect of government ownership. The findings showed that there is no relationship between government ownership and dividends when using the DPS as the dependent variable. However, when DPR is used, the result showed that government ownership could affect the dividend policy. Furthermore, it is found that privately funded government agencies were more likely to affect dividends. This result indicates that these government agencies influence the proportion of earnings distribution or the payable amount rather than the amount of dividend per unit of shares.